2010
DOI: 10.1177/159101991001600306
|View full text |Cite
|
Sign up to set email alerts
|

Triple Coaxial Catheter Technique for Transfacial Superior Ophthalmic Vein Approach for Embolization of Dural Carotid-Cavernous Fistula

Abstract: We report a triple coaxial catheter technique to facilitate the venous access to the superior ophthalmic vein during transvenous embolization of dural carotid-cavernous fistula (DCCF) via the transfacial venous route. Two patients with transvenous embolization of DCCFs by coils were treated with transfacial superior ophthalmic vein (SOV) approach by the triple coaxial catheter technique. The triple coaxial catheter system consisted of a 6F guiding catheter as the outer catheter and a 4F guiding cathet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…In this circumstance, establishment of an angiographic road map may be a great help to define the venous anatomy of the FV-EJV. In addition, a tortuous and looping FV may be found at at its insertion to the jugular vein; to support the microcatheter during navigation, 4F and 6F coaxial guiding catheters with engagement of the 4F tip at the orifice of the FV can be applied (16). Another common challenge of trans-FV embolization is advancement of the microcatheter from the FV to the angular vein and then to the SOV because of marked tortuous venous structures in these segments.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In this circumstance, establishment of an angiographic road map may be a great help to define the venous anatomy of the FV-EJV. In addition, a tortuous and looping FV may be found at at its insertion to the jugular vein; to support the microcatheter during navigation, 4F and 6F coaxial guiding catheters with engagement of the 4F tip at the orifice of the FV can be applied (16). Another common challenge of trans-FV embolization is advancement of the microcatheter from the FV to the angular vein and then to the SOV because of marked tortuous venous structures in these segments.…”
Section: Discussionmentioning
confidence: 98%
“…These venous variations occurred at a higher rate in our series than in previously published series and sporadic observations and led to initial erroneous placement of the guiding catheter and microcatheter in the IJV for trans-FV embolization in our first 2 CCF cases (Figures 1 and 3). Yuen et al (16) reported 2 cases of indirect CCFs in which trans-FV embolization was performed. The trans-EJV route was used in 1 case, and the trans-IJV route was used in the second case.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, it has been increasingly reported that the support force and manipulability can be obtained by the use of a multiple coaxial system. [24][25][26] In our patient, since the shunt point could be approached by recanalizing the occluded access route relatively safely with a quadriaxial system, selective embolization was possible. While consideration of the increase in the size of the puncture orifice is necessary in using a multiple coaxial system, it is considered to be more adoptable for TVE because the procedure is less stressful compared with transarterial embolization regarding the invasiveness and postoperative hemostasis.…”
Section: Discussionmentioning
confidence: 99%
“…By the transfacial vein approach through the superior ophthalmic vein, to circumvent this problem, catheter navigation using a triple coaxial system has been attempted. 10,12) According to previous reports, penetration of the micro-catheter to the SOV and cavernous sinus could be supported by guiding a 4 Fr DAC to a point near the angular vein by a triple coaxial system using a 6 Fr guiding catheter with a 4 Fr DAC, and satisfactory embolization could be achieved. There have been other reports of the use of triple coaxial systems, but, in all these reports, the DAC was navigated only to a point near the angular vein and not beyond the SOV 10,12) because of the difficulty in access due to meandering of the angular vein and obstruction of venous drainage during treatment due to DAC insertion.…”
Section: Discussionmentioning
confidence: 99%
“…Various alternative access routes have been reported in case the trans-IPS approach is difficult to use. They include the facial vein, [10][11][12] is, a Target 360 Ultra soft (Stryker) 2 mm × 3 cm and a Target 360 nano 2 mm × 3 cm, were used. The procedural time was 2 hours and 45 minutes, and the radiation exposure was AP: 1629 mGy and Lat: 780 mGy.…”
Section: Endovascular Treatmentmentioning
confidence: 99%